Predictive Model of The Factors Involved in Cyberbullying of Adolescent Victims - Estrada-Vidal, Ligia Isabel; Epelde-Larrañaga, Amaya; Chacón-Borrego, Fátima (Frontiers in Psychology, 2022)
The development of Information and Communication Technologies has favoured access to technological resources in adolescents. These tools provide access to information that can promote learning. However, they can also have a negative effect against people, as they can be used with other functionality, in which cyberbullying situations are caused during the interactions that arise when using social networks. The objective of this study was to determine the predictive value of the role of cyberbullying victims based on variables related to other roles involved in cyberbullying and bullying (aggressors and witnesses), as well as personal characteristics (sex and age), contextual characteristics (type of educational school in which they are attending) and positive teamwork habits. (cooperation, responsibility, dialogue, listening, respect). Information was collected from 227 students of the educational stages of Primary Education and Secondary Education, aged between 11 and 15 years, in a city with a high index of cultural diversity. The step-by-step technique was used to build the regression model. The results indicate that the model has a good goodness of fit coefficient (adjusted R2: 0.574; p <0.001). The role of cyber-bully is the most important predictive variable of the role of the victim in cyberbullying and, to a lesser extent, the role of the witness in cyberbullying, the role of the witness in bullying and the role of the victim of bullying. The role of the bullying aggressor and the variables sex, age, type of educational centre and teamwork habits are excluded in the predictive model.